2021
DOI: 10.3389/fonc.2021.676598
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Plus Chemotherapy Versus Surgery Alone for Limited-Stage Small-Cell Lung Cancer: A Population-Based Survival Outcome Analysis

Abstract: IntroductionFor patients with limited-stage small-cell lung cancer (LS-SCLC), effective treatment methods still remain a clinical challenge. The aim of this study is to evaluate the survival outcome of surgery plus chemotherapy vs. surgery alone in patients with LS-SCLC.MethodsLS-SCLC patients selected from the Surveillance, Epidemiology and End Results (SEER) database diagnosed between January 1, 2004, and December 31, 2015. Comparison of overall survival (OS) and cancer-specific survival (CSS) between two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previously published studies have demonstrated that patients with untreated limited and extensive SCLC (LD-SCLC and ED-SCLC) have an OS of about 6 and 2 months, respectively, and more than 80% of the patients undergoing standard therapies died within 2 years after diagnosis (8,9). For early-stage SCLC, particularly with no regional lymph node involvement, surgery combined with chemotherapy was the standard therapeutic regimen, and was found to significantly prolong OS (10)(11)(12). At the time of diagnosis, more than one third of patients who developed hilar and/or mediastinal lymph node (N1 and N2) involvement, which was defined as locally advanced SCLC (LA-SCLC) (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies have demonstrated that patients with untreated limited and extensive SCLC (LD-SCLC and ED-SCLC) have an OS of about 6 and 2 months, respectively, and more than 80% of the patients undergoing standard therapies died within 2 years after diagnosis (8,9). For early-stage SCLC, particularly with no regional lymph node involvement, surgery combined with chemotherapy was the standard therapeutic regimen, and was found to significantly prolong OS (10)(11)(12). At the time of diagnosis, more than one third of patients who developed hilar and/or mediastinal lymph node (N1 and N2) involvement, which was defined as locally advanced SCLC (LA-SCLC) (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Ye and colleagues conducted a retrospective cohort study utilizing the SEER database. Their findings suggested that among stage I and II SCLC patients, those who underwent surgery combined with chemotherapy exhibited a longer OS compared to those who underwent surgery alone [ 25 ]. Other pertinent studies have consistently shown the survival advantages associated with adjuvant chemotherapy in patients with resected LS-SCLC [ 26 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…And staying local for treatment can also save on the additional costs associated with cross-regional treatment. Regarding medical costs( ), the treatment expenses for patients in the surgical phase are significantly lower than for those requiring chemotherapy, targeted therapy, or immunotherapy ( 64 , 65 ), thus local treatment is advisable for patients in the surgical phase. Non-surgical patients, in search of better health insurance reimbursement policies, might choose to travel to regions with a broader coverage of health insurance.…”
Section: Discussionmentioning
confidence: 99%